Health literacy: exploring disparities among college students - Jehad A. Rababah; Mohammed M. Al-Hammouri; Barbara L. Drew; Mohammed Aldalaykeh (BMC, 2019)
Abstract Background Health literacy is a multidimensional concept that is considered a primary public health concern. This concept is often neglected in research, and the evidence regarding health literacy in college students is limited. The aim of this study was two-fold: to determine the needs and limitations of health literacy among college students and to explore the relationships among the nine dimensions of health literacy and sociodemographic factors, including age, gender, nationality, year of study, field of study, smoking status, history of chronic diseases, use of on-campus gym, and the intention to exercise on-campus. Methods This study was conducted using a cross-sectional approach. A total of 520 college students participated in this study. The average age was 21.03 years (SD = 2.29), with 47.5% males and 52.5% females. Data were collected using a demographics questionnaire and the Health Literacy Questionnaire (HLQ). In addition to descriptive statistics, multivariate analysis of variance (MANOVA) and follow-up analyses were performed to explore any statistically significant mean differences among levels of health literacy and sociodemographic factors. Results The levels of health literacy on the nine HLQ scales were lower than the levels reported in the literature. Multivariate analysis showed a significant effect of age, gender, smoking status, year of study, and field of study on the level of health literacy. Follow-up analyses revealed that female students, students from the health-related faculties, and those who do not smoke have higher levels of health literacy compared to their counterparts. A detailed comparison between the levels of the HLQ scales was made based on students' demographic characteristics. The field of study had the most prominent effect on the level of college students' health literacy; mean differences were statistically significant (p < .001), and effect sizes were large (ranging from .66 to 1.35 for the nine scales of the HLQ). Conclusion College students' health literacy is influenced by demographic characteristics. Such variations could amplify some of the existing health disparities. The implications of the findings on health, health promotion, and interprofessional education are discussed.